A dual-functional device based on CB/PVDF@BFP for solar-driven water purification and water-induced electricity generation - Huang, Jiangchao (2023)
The efficient utilization of low-grade thermal energy to produce clean water or electricity is important because it potentially relieves our demand on limited natural water and energy resources. Here, we propose a dual-functional device to couple solar-driven water evaporation and evaporation-induced power generation for concurrent production of clean water and green electricity. Our strategy involves the fabrication of an asymmetric, dual-layered structure by spraying a carbon black/polyvinylidene fluoride mixture onto bamboo filter paper (CB/PVDF@BFP). The upper CB/PVDF layer serves as a light-to-thermal transducer for instantaneous heating, while the bottom BFP layer functions as a hydrophilic porous platform to boost water uptake and transfer. Moreover, water evaporation drives capillary flow of ions on the conductive CB/PVDF layer to create a pseudostream that can be harnessed for power generation. Notably, our dual-functional device delivers a fast water evaporation rate of 1.44 kg m−2 h−1 and a high energy utilization rate of 92% under one sun, beyond the previous carbon-based reports. Through this solar-driven water evaporation process, we achieve the efficient desalination of artificial seawater and decontamination of organic-polluted water by up to 99.8% and nearly 100%, respectively. Our device also concurrently produces high, consistent evaporation-induced electrical outputs with VOC and ISC of 0.32 V and 1.5 μA, respectively. The generated electrical outputs can be easily stored by charging a capacitor to over 1.5 V within 15 minutes and be subsequently utilized on demand to power common household electronics. By enabling the efficient coupling of multiple solar-driven processes, our work will catalyze the design of next-generation multifunctional devices to ensure electricity and potable water are easily accessible by everyone, especially remote areas without power stations and/or water treatment facilities.